Iluminación con tecnología led para la cancha de fútbol del corregimiento de Cornejo Norte de Santander - Garcia Noriega, Ronald Enrique (Universidad Antonio Nariño, 2021)
The integral Work of degree consisted in the projection of the lighting system using LED technology for the soccer field of the township of Cornejo, the municipality of San Cayetano, north of Santander, Colombia.